Long-term cardiac monitoring in older adults with unexplained falls and syncope. Issue 9 (28th January 2016) - Bhangu, Jaspreet; McMahon, C Geraldine; Hall, Patricia; Bennett, Kathleen; Rice, Ciara; Crean, Peter; Sutton, Richard; Kenny, Rose-Anne
Abstract : Aims: Unexplained falls account for 20% of falls in older cohorts. The role of the implantable loop recorder (ILR) in the detection of arrhythmias in patients with unexplained falls is unknown. We aimed to examine the diagnostic utility of the ILR in detection of arrhythmogenic causes of unexplained falls in older patients. Methods: A single centre, prospective, observational cohort study of recurrent fallers over the age of 50 years with two or more unexplained falls presenting to an emergency department. Insertion of an ILR (Reveal, Medtronic, Minnesota, USA) was used to detect arrhythmia. The primary outcome was detection of cardiac arrhythmia associated with a fall or syncope. The secondary outcome was detection of cardiac arrhythmia independent of falls or syncope, and falls or syncope without associated arrhythmia. Results: Seventy patients, mean age 70 years (51–85 years) received an ILR. In 70% of patients cardiac arrhythmias were detected at a mean time of 47.3 days (SD 48.25). In 20%, falls were attributable to a modifiable cardiac arrhythmia; 10 (14%) received a cardiac pacemaker, 4 (6%) had treatment for supraventricular tachycardia. Patients who had a cardiac arrhythmia detected were more likely to experience a further fall. Conclusions: 14 (20%) patients demonstrated an arrhythmia which was attributable as the cause of their fall. Patients who have cardiac arrhythmia are significantly more likely to experience future falls. Further research is important to investigate if early detection of arrhythmogenic causes of falls using the ILR prevents future falls in older patients.